Negative equity and foreclosure: Theory and evidence - Christopher L. Foote; Kristopher Gerardi; Paul S. Willen (Federal Reserve Bank of Boston, 2008)
Millions of Americans have negative housing equity, meaning that the outstanding balance on their mortgage exceeds their home's current market value. Our data show that the overwhelming majority of these households will not lose their homes. Our finding is consistent with historical evidence: we examine more than 100,000 homeowners in Massachusetts who had negative equity during the early 1990s and find that fewer than 10 percent of these owners eventually lost their home to foreclosure. This result is also, contrary to popular belief, completely consistent with economic theory, which predicts that from the borrower's perspective, negative equity is a necessary but not a sufficient condition for foreclosure. Our findings imply that lenders and policymakers face a serious information problem in trying to help borrowers with negative equity, because it is difficult to determine which borrowers actually require help in order to prevent the loss of their homes to foreclosure.
Keywords: D11; D12; G21; R20; 330; Hypothek; Insolvenz; Immobilienpreis; Eigenkapital; Massachusetts